Evaluate: ∫ 0 ∞ ( 1 − erf ( x ) ) d x
Notation: erf ( x ) = π 2 ∫ 0 x e − t 2 d t denotes the error function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that 1 − erf ( x ) = π 2 ∫ 0 ∞ e − t 2 d t − π 2 ∫ 0 x e − t 2 d t = π 2 ∫ x ∞ e − t 2 d t so that ∫ 0 ∞ ( 1 − erf ( x ) ) d x = ∫ 0 ∞ π 2 ∫ x ∞ e − t 2 d t d x = π 2 ∫ 0 ∞ ∫ 0 t e − t 2 d x d t = π 2 ∫ 0 ∞ t e − t 2 d t = π 2 ∫ 0 ∞ 2 1 e − u d u = π 1 [ − e − u ∣ ∣ 0 ∞ = π 1 ≈ 0 . 5 6 4 1 9
In the second line how did you intertwine dx and dt?
Log in to reply
I changed the order of integration.
First note that the integrand e − t 2 is never negative, which means we can change the order of integration (for those interested, this is a sufficient, not a necessary, condition).
Then to find the new limits, note that the iterated integral ∫ 0 ∞ ∫ x ∞ e − t 2 d t d x corresponds to integrating over the region 0 ≤ x ≤ t < ∞ in the x t -plane. Using this inequality, we can see the limits on x are x = 0 and x = t , giving ∫ 0 ∞ ∫ 0 t e − t 2 d x d t as an equivalent iterated integral.
Problem Loading...
Note Loading...
Set Loading...
I = ∫ 0 ∞ ( 1 − erf ( x ) ) d x = ∫ 0 ∞ erfc ( x ) d x = x erf ( x ) ∣ ∣ ∣ ∣ 0 ∞ − ∫ 0 ∞ π 2 x e − x 2 d x = x → ∞ lim x 1 erf ( x ) − 0 − π e − x 2 ∣ ∣ ∣ ∣ 0 ∞ = x → ∞ lim − x 2 1 π 2 e − x 2 − 0 − 0 + π 1 = 0 + π 1 ≈ 0 . 5 6 4 Complimentary error function erfc ( z ) = 1 − erf ( z ) erfc ( z ) = π 2 ∫ z ∞ e − t 2 d t By integration by parts A 0/0 case, L’H o ˆ pital’s rule applies. Differentiate up and down w.r.t. x